2018
DOI: 10.18203/2320-6012.ijrms20182287
|View full text |Cite
|
Sign up to set email alerts
|

Platelet indices evaluation in patients with dengue fever

Abstract: Background: Platelet indices (PIs)-Platecrit, mean platelet volume (MPV) and platelet distribution width (PDW)-are a group of platelet parameters obtained as a part of complete blood count using automated hematology analyzers. Evidence suggests that PIs may have diagnostic and prognostic value in febrile thrombocytopenia. This study aims to understand the profile of PIs in dengue fever. Aims and objectives was to study the platelet indices in patients with dengue fever.Methods: The present study is a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 20 publications
8
30
0
Order By: Relevance
“…We can see from table 2, the value of mean MPV increases as the platelets count increases. This is in accordance with the study conducted by Bashir, et al, 2015, Anuradha, et al, 2014, Navya, et al, 2016and Mukker, et al, 2018 They also observed low value of mean platelet volume (MPV) with low platelet count. Navya, et al,2016 in their study group of 100 patients, saw a mean MPV of <9 fl in 72% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…We can see from table 2, the value of mean MPV increases as the platelets count increases. This is in accordance with the study conducted by Bashir, et al, 2015, Anuradha, et al, 2014, Navya, et al, 2016and Mukker, et al, 2018 They also observed low value of mean platelet volume (MPV) with low platelet count. Navya, et al,2016 in their study group of 100 patients, saw a mean MPV of <9 fl in 72% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed a significantly low MPV in patients with platelet count below 20,000/cu.mm compared to patients with higher platelet counts. Similar result was found by Mukker P, et al in their retrospective observational study [27]. We found significant fall in MPV on the previous day of the day on which platelet count came below 20,000/cu.mm, thus indicating that the significant fall in platelet count may be predicted by looking at serial MPV.…”
Section: Statement Of Equal Author's Contributionsupporting
confidence: 91%
“…In a study by Camara-Lemarroy et al, MPV had 82% sensitivity and 78% and specificity to differentiate bacterial meningitis from tuberculous meningitis [20]. MPV as a utility in dengue has varied with different studies [14]. In Brazil, a higher MPV was found with the first vivax malaria infection and those with symptoms for >3 days [20].…”
Section: Discussionmentioning
confidence: 99%
“…PDW has been used in the identification of pulmonary tuberculosis and acute cholecystitis and organ failure in acute pancreatitis [25]. Increased PDW was seen in ascitic fluid infection, vivax malaria, dengue, and septic shock [5,9,13,14]. PDW was reduced in deep-seated surgical site infection in orthopaedic patients and children with Gram-positive organism-related urinary tract infection [6,10].…”
Section: Discussionmentioning
confidence: 99%